Acute Renal Failure in a Patient with Rivaroxaban-Induced Hypersensitivity Syndrome: A Case Report with a Review of the Literature and of Pharmacovigilance Registries - Gisela Marcelino; Ould Maouloud Hemett; Eric Descombes (Case Reports in Nephrology)
Direct oral anticoagulants (DOACs) are among the most commonly prescribed medications, and DOAC-associated kidney dysfunction may be a problem that is underrecognized by clinicians. We report on the case of an 82-year-old patient who, two weeks after the prescription of rivaroxaban for atrial fibrillation, was hospitalized for a drug-induced hypersensitivity syndrome whose main clinical manifestations were low-grade fever with a petechial rash in the legs and acute renal failure (ARF). Within one week after rivaroxaban withdrawal, the patient’s clinical condition improved and the renal function normalized. In a review of the literature, we only found five case reports of rivaroxaban-related ARF: two patients had tubulo-interstitial nephritis (TIN), two had anticoagulant-related nephropathy (ARN), and the last one had IgA nephropathy. As some recent publications suggest that kidney injury due to anticoagulation drugs may be largely underdiagnosed, we also analyzed the data from the VigiAccess database, the World Health Organization pharmacovigilance program that collects drug-related adverse events from 134 national registries worldwide. Among all the rivaroxaban-associated adverse events reported in VigiAccess since 2006, 4,323 (3.5%) were renal side effects, of which 2,351 (54.3%) were due to unspecified ARF, 363 (8.4%) were due to renal hemorrhage (characteristically associated with ARN), and 24 (0.6%) were due to TIN. We also compared these results with those reported in VigiAccess for other DOACs and vitamin K antagonists. This analysis suggests that the frequency of renal adverse events associated with rivaroxaban and other DOACs may be appreciably higher than what one might currently consider based only on the small number of fully published cases.